Walimatus Safar: Strengthening Mental and Spiritual Readiness for Prospective Hajj Pilgrims - Alif Daffa Ryanditya; Anasom Anasom (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to analyze the impact of the Walimatus Safar tradition on the mental and spiritual readiness of prospective Hajj pilgrims before their departure for the Holy Land. This tradition is a deeply rooted socio-religious practice in Muslim society and is often understood as a form of prayer, support, and gratitude before the Hajj pilgrimage. This study seeks to explore the meaning directly experienced by prospective pilgrims and assess the tradition's contribution to strengthening their psychological and spiritual readiness. The study used a qualitative, phenomenological approach to understand participants' subjective experiences. Data were collected through in-depth interviews, direct observation of the Walimatus Safar ceremony, and reflections on the researcher's experiences. Analysis was conducted by interpreting these experiences to identify key themes related to mental and spiritual readiness. The results show that Walimatus Safar plays a significant role in enhancing the mental readiness of prospective Hajj pilgrims. Social support from family, relatives, and the community provides emotional reinforcement that can reduce anxiety, foster a sense of calm, and increase self-confidence as one faces the long and challenging pilgrimage. Furthermore, the atmosphere of togetherness created also strengthens the pilgrims' psychological resilience. From a spiritual perspective, this tradition serves as a reflective moment that encourages the internalization of the values of sincerity, humility, and an awareness of the meaning of the Hajj pilgrimage as a divine calling. The Walimatus Safar (preparation for the journey) helps prospective pilgrims affirm their intentions, deepen their religious awareness, and strengthen their commitment to carrying out the pilgrimage earnestly. Thus, this tradition is not merely ceremonial but serves an essential psychological and spiritual function in the Hajj preparation process.